The application of the international trading and investment theories on international automobile business: Lesson from 2 case studies; Proton and Toyota - Mohammad Rahimee, Ibrahim (2010)
In the 21st century, there are many domestic companies who have strived try to enter the foreign market. All the existing multinational company would face challenges from this development. Some of the challenges that theses multinational companies would face includes technology and financial. Several theories includes mercantilism theory that was used widely in 17th century, absolute advantage theory that explain how free trade will affect the trade flow, comparative advantage theory, Heckscher-Ohlin theory, product life theory and other international investment theories have been used to study and understand international investment.